MODELING THE INFLUENCE OF MODERN FACTORS ON EMPLOYMENT TRANSFORMATION IN THE BANKING SECTOR - Domuz, O. (Socio-economic relations in the digital society, 2021)
The study proposed a schematic model of the impact of the financial crisis, the COVID-19 pandemicand the digitalization of the economy on the transformation of employment in the banking sector, whichincludes two levels of impact of specific markets and specific factors on the transformation of employment inthe banking sector. According to the proposed model, the peculiarities of the influence of each factor a teachlevel are determined, in particular: the first level of influence characterizes the diversity of each factor on certainmarket types related to the activities of banking institutions, to the analyzed factors. It is determined that thefinancial capital market, foreign exchange market and labor market react most strongly to the impact of thefinancial crisis; the impact of the COVID-19 pandemic factor — the health care market, the information marketand the labor market; the factor of digitalization of the economy causes changes in the market of innovations,the market of educational services, the information market and the labor market. This points to the close linkbetween the impact of global macroeconomic factors and employment as one of the main elements of the labor market. According to the results of testing the model, changes in the structure of employment in thebanking sector under the influence of the financial crisis, the COVID-19 pandemic and the digitalization ofthe economy are schematically reflected and analyzed. It was found that under the influence of the financialcrisis, the employment policy of Ukrainian banks was aimed at the physical reduction of all types and formsof employment, and the structure of non-standard employment remained conservative and unbranched; Theimpact of the COVID-19 pandemic factor is accompanied by the active introduction and spread of remoteemployment in all are as of banking, the application of which has shown a number of advantages over traditionalforms of employment and expanding the range of other non-standard forms of employment. For the first timein all the practice of economic activity of banks. The impact of the factor of digitalization of the economy on thestructure of employment in the banking sector is characterized by the promotion of forms and types of nonstandard employment (freelance and outsourcing). It is determined that the active use of digital technologies inthe banking sector has changed the very structure of work, deepening the imbalance between professions.
Keywords: employment; banking sector; remote employment; digitalization; financial crisis; COVID-19; economic model